Relationship between epicardial adipose tissue thickness and epicardial adipocyte size with increasing body mass index. (2nd January 2019) - Aitken-Buck, Hamish M.; Moharram, Mohammed; Babakr, Aram A; Reijers, Robin; Van Hout, Isabelle; Fomison-Nurse, Ingrid C.; Sugunesegran, Ramanen; Bhagwat, Krishna; Davis, Phillip J; Bunton, Richard W.; Williams, Michael J. A.; Stiles, Martin K.; et al.
ABSTRACT: Macroscopic deposition of epicardial adipose tissue (EAT) has been strongly associated with numerous indices of obesity and cardiovascular disease risk. In contrast, the morphology of EAT adipocytes has rarely been investigated. We aimed to determine whether obesity-driven adipocyte hypertrophy, which is characteristic of other visceral fat depots, is found within EAT adipocytes. EAT samples were collected from cardiac surgery patients (n = 49), stained with haematoxylin & eosin, and analysed for mean adipocyte size and non-adipocyte area. EAT thickness was measured using echocardiography. A significant positive relationship was found between EAT thickness and body mass index (BMI). When stratified into standardized BMI categories, EAT thickness was 58.7% greater (p = 0.003) in patients from the obese (7.3 ± 1.8 mm) compared to normal (4.6 ± 0.9 mm) category. BMI as a continuous variable significantly correlated with EAT thickness (r = 0.56, p < 0.0001). Conversely, no correlation was observed between adipocyte size and either BMI or EAT thickness. No difference in the non-adipocyte area was found between BMI groups. Our results suggest that the increased macroscopic EAT deposition associated with obesity is not caused by adipocyte hypertrophy. Rather, alternative remodelling via adipocyte proliferation might be responsible for the observed EAT expansion.